Pengelolaan Dana Donasi di Panti Asuhan Berkah Palangkaraya - Abdul Karim; Slamet Riyadi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Fund management in an orphanage is very important to see the mechanism starting from how the process of obtaining funds, the use of funds, to reports and accountability, therefore this study aims to determine how the process of obtaining funds, how the use of funds, and how reports and accountability of funds at the Blessing orphanage institution Palangka Raya. The method used in this research is a descriptive approach qualitative method in which researchers use field research techniques. The results of this study are in terms of obtaining funds, the orphanage obtains funds from several sources, namely the government through Social Services, donors, and charity cities distributed through PUB licenses. The funds that have been received are then managed by the orphanage management based on the needs of foster children. Accountability of fund management, the orphanage management realizes through making routine reports every month according to real conditions. To realize transparency, so far it has been realized by providing report results to regular donors and to the government.